Frequency selective rasorber with high temperature resistance and mechanical bearing characteristics based on double-layer metasurface regulation - Zhimin An; Tengteng Xu; Yiping Li; Rubing Zhang; Binzhen Zhang (Materials & Design)
It is crucial to design and implement a stealth radome in order to increase the overall stealth of weaponry. A multi-station radar network system’s effect is greatly diminished by the traditional stealth radome, which depends on the reflection of enemy radar waves in the non-incident direction to achieve the stealth of a single radar base station. This method is unable to produce a complete stealth effect. In this work, the frequency selective rasorber (FSR) is theoretically analyzed. Based on this, a frequency-selective surface (FSS) and a patterned resistor film (PRF) are used to design the low-frequency transmission/high-frequency absorption (T-A) structure, which is then confirmed through simulation. To better meet practical application requirements, considering thermal resistance and mechanical load-bearing performance, the integrated molding process of fiber ceramic-based sandwich structure was developed and successfully obtained the high-strength FSR structure, which achieves high-frequency wave transmittance of 15.5–15.8 GHz, low-frequency wave absorption of 5.1–12.6 GHz. After 800 °C thermal treatment, the metastructure maintained excellent transmission coefficients at passband frequencies, demonstrating remarkable stability. At the same time, it has excellent mechanical strength (flexural strength of 43.9 MPa). It provides a new and effective way to explore stealth systems using hypersonic vehicle antennas.